Effect of coenzyme Q10 supplementation on oxidative stress and clinical outcomes in patients with low levels of coenzyme Q10 admitted to the intensive care unit. (12th July 2021) - Hasanloei, Mohammad Amin Valizade; Zeinaly, Aidin; Rahimlou, Mehran; Houshyar, Hadi; Moonesirad, Solma; Hashemi, Reza
Abstract: Today, trauma is known to be the third leading cause of death in most countries. Studies have demonstrated below-normal plasma levels of antioxidants in trauma patients. The present study aimed to assess the efficacy of Coenzyme Q10 (CoQ10) on oxidative stress, clinical outcomes and anthropometrical parameters in traumatic mechanical ventilated patients admitted to the intensive care unit. Patients were randomised to receive sublingual CoQ10 (400 mg/d) or placebo for 7 d. Primary and secondary outcomes were measured at the baseline and end of the study. We enrolled forty patients for this trial: twenty in the CoQ10 group and twenty in the placebo group. There was not any significant difference in the baseline variables ( P > 0⋅05). At the end of the study, CoQ10 administration caused a considerable reduction in the Malondialdehyde (MDA) and Interleukin 6 (IL-6) concentrations ( P < 0⋅001), Glasgow Coma Score (GCS; P = 0⋅02), ICU and hospital length of stay and mechanical ventilation (MV) duration ( P < 0⋅001). We found that CoQ10 administration could increase Fat-Free Mass ( P < 0⋅001) (FFM; P = 0⋅04), Skeletal Muscle Mass (SMM; P = 0⋅04) and Body Cell Mass (BCM) percent ( P = 0⋅03). There was not any significant difference in other factors between the two groups ( P > 0⋅05). CoQ10 administration has beneficial effects on patients with traumatic injury and has no side effects. However, since the possibility of the type II error was high, the outcomes on the duration of MV, ICU stay and hospital stay, and GCS may very well be false positives.